Gambaran kejadian bayi berat lahir rendah pada ibu usia reproduktif dan usia berisiko di poned - Surya Meka Novita Sari; Sabarrudin Sabarrudin (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Maternal mortality rates and infant mortality rates are very important indicators, with cases in Indonesia still relatively high. Low birth weight (LBW), defined as a birth weight of less than 2500 grams, remains one of the leading causes of infant mortality, accounting for 38.85% of total infant deaths in Indonesia. Purpose: To provide an overview of LBW cases among women of reproductive age (20-35 years) and women of high-risk age (<20 years or >35 years) at PONED. Methods: A descriptive cross-sectional study using secondary data from birth records with a sample of 95 live births. Conducted from November 2018 to February 2019. Results: Of the 7 LBW cases (7.4% of total births), 6 cases (8%) occurred in women of reproductive age and 1 case (6%) in women of high-risk age. This study shows a higher prevalence of LBW in the reproductive age group, which is counterintuitive compared to the general literature that identifies high-risk age as the main risk factor. This is most likely influenced by the numerical dominance of the reproductive age group in the sample, as well as the role of unmeasured confounding factors such as double burden, chronic fatigue, and socioeconomic disparities that affect access to and quality of antenatal care. Conclusion: This study concludes that LBW can occur in both age groups, but in this context, it is more prevalent in mothers of reproductive age. Therefore, a holistic screening approach that focuses on maternal age, as well as improving the quality of comprehensive antenatal care, is very important to reduce the incidence of LBW and improve the health of mothers and babies.